گۆڕینى سه‌راى سلێمانى بۆ مۆزه‌خانه‌ هه‌ڵسه‌نگاندنێكى زانستیانه‌ - فتاح, عثمان توفیق; محمد, علی هجران (Sulaimani Journal for Humanities, 2018)
This article tries to discuss the importance of Slemani Saray Building, history and its architecture. The article's main focus is about converting historic houses into a museum, it's also discusses the strengths and weakness of the Saray building, furthermore, it goes to highlight the main challenges that the museum will may face and suggest how it can tackle them.
Keywords: Slemani Saray; Heritage Museums; Historic Buildings